High-precision lighting for plants: monochromatic red laser diodes outperform LEDs in photosynthesis and plant growth - Li, Lie; Sugita, Ryusei; Yamaguchi, Kampei; Togawa, Hiroyuki; Terashima, Ichiro; Yamori, Wataru (Frontiers in Plant Science, 2025)
The optimization of plant productivity in indoor horticulture relies heavily on artificial light systems, which serve as the primary light source for plant growth. Although light-emitting diodes (LEDs) have been extensively studied in recent decades, there is limited research on laser diodes (LDs). LDs offer several advantages, including single-wavelength coherent light, remote illumination via optical fibers that minimizes heat accumulation at the canopy level, a compact and lightweight design, and enhanced energy efficiency at high input current densities. This study investigated the impact of red LD light on plant photosynthesis and growth, exploring its potential applications in indoor horticulture. The research examined the gas exchange of tobacco plants (Nicotiana tabacum L. cv. Wisconsin-38) under six red LED and LD light sources with varying spectral characteristics. Two specific light sources were selected for further study: LED 664 (emission peak at 664 nm, waveband of 625~678 nm) and LD 660 (emission peak at 660 nm, waveband of 657~664 nm) as they demonstrated the greatest gas exchange efficiency among the tested LED and LD light sources. These two light sources were then evaluated for their effects on photochemical efficiency, carbohydrate accumulation and plant growth. The present study showed that compared with LED 664, LD 660 significantly increased Y(II), qL, and starch accumulation in tobacco leaves. Additionally, after 12 d of continuous irradiation with LD 660, tobacco and Arabidopsis plants exhibited increased photosynthetic capacity. Furthermore, all three investigated species, tobacco, Arabidopsis, and lettuce, showed greater shoot dry weights and leaf areas compared to those under LED 664. These findings suggest that LDs present significant advantages over LEDs for indoor plant production.